Implementation of Quality Management System in Iranian Medical Laboratories - P Dahim; N Safadel; F Rashed Marandi; K Khodaverdian; M Rahnamaye Farzami (Tehran University of Medical Sciences, 2009)
"nReference health Laboratory of Iran (RHL) has been established under the Secretary of Health in 2007. This organization has been developed from integration of Reference laboratories of Iran, Directorate of General Affairs and Laboratory department of CDC. In accordance with policies of Ministry of Health and Medical Education, also Millennium Development Goals and requirements of IHR the RHL has highlighted his main goal as "Quality Improvement of Medical Laboratory Network". In order to achieve this goal as soon and efficient as possible, RHL has tried to launch Quality Management system in medical laboratories. After studying and analyzing the situation in the country RHL has tried by using ISO 15189 which is an successful international standard to draw national standards and write necessary manuals, guidelines and checklists. For a successful implementation and detailed managerial observance, three phases were designed: Training, Stepwise implementation of standard requirements in the laboratories, accreditation of laboratories. After one year of training and sending out national standards and guidelines, the RHL is in the middle of the second phase "implementation".